PEMBUATAN GAME BAKEY PADA PLATFORM ANDROID - Eric Eric; Darius Andana H; Ruby Chrissandy (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Learning by playing is a good method to learn something. One of many things that can be learnt is business. Learning how to maintain a business can be done by playing simulation games. This kind of game simulates condition in real life . Bakery is one of businesses that can be implied into this kind of game. To manage a bakery is not an easy task, there are many points that have to be prepared, like building maintenance, staffs salary, advertising and most of all is the strategy to get many profits. Bakey is a simulation game about bakery that is written in ActionScript 3.0 with Adobe Flash. Key words Adobe Flash, Android, Bakery, Simulation Game